Cytokine Profile in Chronic Periodontitis Patients with and without Obesity: A Systematic Review and Meta-Analysis. (26th September 2016) - Akram, Zohaib; Abduljabbar, Tariq; Abu Hassan, Mohamed Ibrahim; Javed, Fawad; Vohra, Fahim
Abstract : To investigate the cytokine profile as biomarkers in the gingival crevicular fluid (GCF) of chronic periodontitis (CP) patients with and without obesity, MEDLINE/PubMed, EMBASE, ScienceDirect, and SCOPUS databases were combined with handsearching of articles published from 1977 up to May 2016 using relevant MeSH terms. Meta-analyses were conducted separately for each of the cytokines: resistin, adiponectin, TNF- α, leptin, IL-6, IL-8, and IL-1 β . Forest plots were produced reporting standardized mean difference of outcomes and 95% confidence intervals. Eleven studies were included. Three studies showed comparable levels of leptin among obese and nonobese patients with CP. Four studies reported comparable levels of interleukin- (IL-) 6 and resistin whereas five studies reported comparable levels of adiponectin. Two studies reported similar levels of CRP in patients with periodontitis with and without obesity. One study showed higher levels of tumor necrosis factor-alpha in obese patients with CP. One study showed higher levels of IL-1 β and IL-8 in obese patients with CP. The level of localized periodontal inflammation may have a greater influence on the GCF proinflammatory biomarker levels as compared to systemic obesity. Whether patients having chronic periodontitis with obesity have elevated proinflammatory GCF biomarkers levels compared to nonobese individuals remains debatable.